Greed, grievance, and the displacement of identity: Courses of community conflict in the Mahaweli resettlement scheme in Sri Lanka - Epa, Pulsie (Dynamics of Rural Society Journal, 2026)
This study investigates the interplay of greed, grievance, and identity displacement as drivers of community conflict within the Mahaweli Resettlement Scheme in Sri Lanka. The main objective of this research was to identify the central drivers of conflict that arose within the resettled Vedda community. The main research question explores how resource competition and socio-political marginalization shape inter-group tensions among the resettled and Indigenous population. Employing a mixed-methods approach, the study draws on archival research, semi-structured interviews with 35 community members and local officials, and non-participant observation in Hennanigala, Mahaweli C zones. Further, surveys are used for data collection. Thematic analysis revealed that social, economic, political, and environmental factors were the primary contributors to conflict. The findings indicate that within these main drivers, factors such as cultural issues, social adaptability, land use patterns, traditional ways of life, poverty, modern development practices, macro-level policy design, weak implementation, the intervention of powerful political groups, administrative patterns, resource scarcity, land and forest encroachment, overconsumption of common pool resources, and resource abundance were identified as key leverage points. Further, while competition over land and water (greed) initially triggered disputes, deeper grievances related to perceived inequalities in state resource allocation and cultural marginalization intensified hostilities. Resettled Sinhalese farmers, often favored by state policies, were viewed with suspicion by the Vedda community, leading to identity-based polarization. Furthermore, the forced reconfiguration of traditional settlement patterns disrupted longstanding social networks, exacerbating mistrust and reducing avenues for conflict resolution. This study contributes to scholarship on internal displacement and postcolonial development by highlighting how top-down resettlement projects, even when framed as economic development, can produce long-term socio-fragmentation. It underscores the importance of inclusive planning and culturally sensitive governance in multi-cultural rural transformation programs.